O pieczęci miejskiej Uniejowa z pierwszej połowy XVI wieku - Adamczewski, Marek (Biuletyn Uniejowski, 2012)
The heraldic arms of Uniejów have been the subject of intensive studies and monographic publicatins, and review works on town seals from Greater Poland contain extensive sections on the cross and three lilies of Uniejów. A key issue in the research on Uniejów’s identifying logo is the origin of the town seal. In the first half of the 16th century, five towns in the Gniezno Chapter within the historical area of Greater Poland (Grocholice, Grzegorzew, Piątek, Turek and Uniejów) had identical seals made, in which the graphic element – a Latin cross and three double lilie, which is the emblem of the Gniezno Chapter coat of arms – was combined with a pious motto and the name of the respective town. The uniform design for the seals was authored by cathedral canons from Gniezno. The style of the seal as well as preserved documents containing stamps of the seal indicate that it was made in the 1st half of the 16th century.